# |
ODE |
Mathematica |
Maple |
\[
{}5 y^{\prime \prime } x +\left (30+3 x \right ) y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } x -\left (x +4\right ) y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime } x -\left (2 x +6\right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\left (3 x^{2}+2 x \right ) y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}x \left (1-x \right ) y^{\prime \prime }-3 y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } x +y^{\prime }-x y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-x y^{\prime }+\left (x^{2}+1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\left (x^{2}-3 x \right ) y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x^{2} y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\left (2 x^{2}-3 x \right ) y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x \left (1+x \right ) y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {9}{4}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-x \left (1+x \right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-x y^{\prime }+\left (x^{2}+1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } x +3 y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } x -y^{\prime }+36 x^{3} y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-5 x y^{\prime }+\left (x +8\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}36 x^{2} y^{\prime \prime }+60 x y^{\prime }+\left (9 x^{3}-5\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}16 x^{2} y^{\prime \prime }+24 x y^{\prime }+\left (144 x^{3}+1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+3 x y^{\prime }+\left (x^{2}+1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{2} y^{\prime \prime }-12 x y^{\prime }+\left (15+16 x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}16 x^{2} y^{\prime \prime }-\left (-144 x^{3}+5\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }-3 x y^{\prime }-2 \left (-x^{5}+14\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+x^{4} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } x +4 x^{3} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } x +2 y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+9 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-x^{\prime }-2 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+8 x^{\prime }+15 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x = \sin \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x = \cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x = \cos \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+9 x = 1
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+3 x = 1
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+3 x^{\prime }+2 x = t
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = 2 x \left (t \right )+y \left (t \right ), y^{\prime }\left (t \right ) = 6 x \left (t \right )+3 y \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+6 x^{\prime }+25 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-6 x^{\prime }+8 x = 2
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-4 x = 3 t
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+8 x = {\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime \prime }+x^{\prime \prime }-6 x^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime \prime \prime }-x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime \prime \prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime \prime \prime }+13 x^{\prime \prime }+36 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime \prime \prime }+8 x^{\prime \prime }+16 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime \prime \prime }+2 x^{\prime \prime }+x = {\mathrm e}^{2 t}
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+13 x = t \,{\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+6 x^{\prime }+18 x = \cos \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+9 x = 6 \cos \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+\frac {2 x^{\prime }}{5}+\frac {226 x}{25} = 6 \,{\mathrm e}^{-\frac {t}{5}} \cos \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}t x^{\prime \prime }+\left (t -2\right ) x^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}t x^{\prime \prime }+\left (3 t -1\right ) x^{\prime }+3 x = 0
\] |
✓ |
✓ |
|
\[
{}t x^{\prime \prime }-\left (4 t +1\right ) x^{\prime }+2 \left (2 t +1\right ) x = 0
\] |
✓ |
✓ |
|
\[
{}t x^{\prime \prime }+2 \left (t -1\right ) x^{\prime }-2 x = 0
\] |
✓ |
✓ |
|
\[
{}t x^{\prime \prime }-2 x^{\prime }+t x = 0
\] |
✓ |
✓ |
|
\[
{}t x^{\prime \prime }+\left (4 t -2\right ) x^{\prime }+\left (13 t -4\right ) x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x = f \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+2 x^{\prime }+x = f \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+13 x = f \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x = \delta \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x = \delta \left (t \right )+\delta \left (t -\pi \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+4 x = 1+\delta \left (t -2\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+2 x^{\prime }+x = t +\delta \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+2 x^{\prime }+2 x = 2 \delta \left (t -\pi \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+9 x = \delta \left (t -3 \pi \right )+\cos \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+5 x = \delta \left (t -\pi \right )+\delta \left (t -2 \pi \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+2 x^{\prime }+x = \delta \left (t \right )-\delta \left (t -2\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x = f \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+6 x^{\prime }+9 x = f \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+6 x^{\prime }+8 x = f \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+8 x = f \left (t \right )
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = y \left (t \right ), y^{\prime }\left (t \right ) = -x \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = y \left (t \right ), y^{\prime }\left (t \right ) = x \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = -2 y \left (t \right ), y^{\prime }\left (t \right ) = 2 x \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = 10 y \left (t \right ), y^{\prime }\left (t \right ) = -10 x \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}\left [x^{\prime }\left (t \right ) = \frac {y \left (t \right )}{2}, y^{\prime }\left (t \right ) = -8 x \left (t \right )\right ]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = 8 y \left (t \right ), y^{\prime }\left (t \right ) = -2 x \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = y \left (t \right ), y^{\prime }\left (t \right ) = 6 x \left (t \right )-y \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = -y \left (t \right ), y^{\prime }\left (t \right ) = 10 x \left (t \right )-7 y \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = -y \left (t \right ), y^{\prime }\left (t \right ) = 13 x \left (t \right )+4 y \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = y \left (t \right ), y^{\prime }\left (t \right ) = -9 x \left (t \right )+6 y \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[10 x_{1}^{\prime }\left (t \right ) = -x_{1} \left (t \right )+x_{3} \left (t \right ), 10 x_{2}^{\prime }\left (t \right ) = x_{1} \left (t \right )-x_{2} \left (t \right ), 10 x_{3}^{\prime }\left (t \right ) = x_{2} \left (t \right )-x_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = -x \left (t \right )+3 y \left (t \right ), y^{\prime }\left (t \right ) = 2 y \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = x \left (t \right )-2 y \left (t \right ), y^{\prime }\left (t \right ) = 2 x \left (t \right )-3 y \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = -3 x \left (t \right )+2 y \left (t \right ), y^{\prime }\left (t \right ) = -3 x \left (t \right )+4 y \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = 3 x \left (t \right )-y \left (t \right ), y^{\prime }\left (t \right ) = 5 x \left (t \right )-3 y \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = -3 x \left (t \right )-4 y \left (t \right ), y^{\prime }\left (t \right ) = 2 x \left (t \right )+y \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = x \left (t \right )+9 y \left (t \right ), y^{\prime }\left (t \right ) = -2 x \left (t \right )-5 y \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = 4 x \left (t \right )+y \left (t \right )+2 t, y^{\prime }\left (t \right ) = -2 x \left (t \right )+y \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = 2 x \left (t \right )+y \left (t \right ), y^{\prime }\left (t \right ) = x \left (t \right )+2 y \left (t \right )-{\mathrm e}^{2 t}]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = 2 x \left (t \right )-3 y \left (t \right )+2 \sin \left (2 t \right ), y^{\prime }\left (t \right ) = x \left (t \right )-2 y \left (t \right )-\cos \left (2 t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right )+2 y^{\prime }\left (t \right ) = 4 x \left (t \right )+5 y \left (t \right ), 2 x^{\prime }\left (t \right )-y^{\prime }\left (t \right ) = 3 x \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[-x^{\prime }\left (t \right )+2 y^{\prime }\left (t \right ) = x \left (t \right )+3 y \left (t \right )+{\mathrm e}^{t}, 3 x^{\prime }\left (t \right )-4 y^{\prime }\left (t \right ) = x \left (t \right )-15 y \left (t \right )+{\mathrm e}^{-t}]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = x \left (t \right )+2 y \left (t \right )+z \left (t \right ), y^{\prime }\left (t \right ) = 6 x \left (t \right )-y \left (t \right ), z^{\prime }\left (t \right ) = -x \left (t \right )-2 y \left (t \right )-z \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = x \left (t \right )-2 y \left (t \right ), y^{\prime }\left (t \right ) = -4 x \left (t \right )+4 y \left (t \right )-2 z \left (t \right ), z^{\prime }\left (t \right ) = -4 y \left (t \right )+4 z \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = y \left (t \right )+z \left (t \right )+{\mathrm e}^{-t}, y^{\prime }\left (t \right ) = x \left (t \right )+z \left (t \right ), z^{\prime }\left (t \right ) = x \left (t \right )+y \left (t \right )]
\] |
✓ |
✓ |
|